HORSE- CATTLE BREEDING OF TAJIKS LIVING IN THE SOUTH OF UZBAEKISTAN - Akhmedov Sardor Sayridin o’g’li (Journal of new century innovations, 2022)
A comparative study of the national Horse-breeding of the Tajik ethnic communities of the Surkhandarya oasis shows that the traditional ethnic aspects. The inhabitants of the oasis go in for horse breeding since the ancient times. Before the beginning of kupkari (goat – breaking competition) the stable man who tests are called testing stable-men.